Balanced Scorecard dalam Manajemen Mutu Pendidikan di MAN 1 Muara Enim - Ana Mawaddah; Hendra Harmi; Sumarto Sumarto (Journal Of Administration and Educational Management (ALIGNMENT), 2023)
The balanced scorecard is a strategy that can be used by educational institutions to improve the quality of education. In its implementation, there are four perspectives; financial, customer, internal processes, and learning and growth perspectives. The purpose of this research is to understand how the implementation of the balanced scorecard in educational institutions. This type of qualitative research with a case study approach. The research is located at MAN 1 Muara Enim. Sources of data were obtained from field observations, interviews with school principals, quality assurance deputy heads, curriculum assistant heads, student affairs assistant heads, deputy public relations heads, and heads of administration, documentation, and there were questionnaires as supporting data distributed to students. The data analysis technique used is data reduction, data display, and conclusion. The results of this study present the balanced scorecard in education quality management at MAN 1 Muara Enim, namely from a financial perspective there is planning, organizing, implementing and supervising the RKAM (Madrasah Work Plan and Budget); service satisfaction perspective, in preparing satisfaction of course requires planning, organizing, implementing and supervising, in the service satisfaction of students towards madrasas it reaches 90.96% with a gap of 9.04% where students are already satisfied with madrasah services even though there are still students who feel dissatisfied; the perspective of the learning process includes planning, organizing, implementing and supervising the learning process in the form of making learning tools up to paying attention to the material and methods to be delivered as well as supervision which aims to improve the learning process of each educator; From the perspective of educators and education staff, there is planning in the form of recruiting educators and students, organizing by sharing among educators and staff, implementation by instilling a work culture, coaching and motivation, as well as supervision carried out by the Assessment Team to assess the performance of educators. Keywords: Balanced Scorecard, Management, Quality of Education